The importance of modern technology advancements in the development of classical Panchakarma instruments - Dwivedi, Pramod C.; Pande, Pulsi; Sharma, Madan M.; Kumar, Amit (International Journal Of Community Medicine And Public Health, 2026)
The ultimate substitute of Ayurvedic treatment is Panchakarma, a specific bio-purificatory and rejuvenating method that involves five grand operations, namely Vamana, Virechana, Basti, Nasya and Raktamokshana. The success of these classical procedures is not based on the skill of the physician and drugs only but also on the accuracy of the instruments (Yantras and Upakaranas) used and the design of the instruments. Historically Panchakarma instruments were made by hand out of natural products, e.g. clay, wood, brass, or animal parts based on the theory named Sukha-Upayoga (easy to use), Kshamata (efficient) and Sthirata (long-lasting) in the writings of Charaka Samhita and Sushruta Samhita. But in the face of the renewed Ayurveda worldwide, the shortcomings of traditional equipment, e.g. the absence of standardization, variation of temperature, hygiene issues, and the reliance on human skill, have aroused the requirement of technology. Background: This review seeks to assess the relevance of the modern technological development on the design, standardisation, and clinical adjustments of classical Panchakarma instruments and in particular, their safety, accuracy, reliability and universal usability. Panchakarma instruments have been undergoing a transformation process that is progressive, which has been achieved by incorporating both engineering and biomedical technology. Added to innovations in the area. Moreover, standardization, documentation of research and global acceptance has become easier due to the introduction of Ayur informatics, sensor-based monitoring, and data-driven SOPs.